Analysis of Student Participation Pursuing Package C in Online Learning During the Covid-19 Pandemic - Artha, I Ketut Atmaja Johny; Widodo, Widodo; Nusantara, Widya; Cahyani, Arini Dwi (Universitas Negeri Semarang, 2022)
The Covid-19 pandemic has limited public service activities, including education. Package C education at CLC has diverse student backgrounds, so educators must make online learning by conducive. The purpose of this study was to describe the level of participation of students pursuing package C in online learning during the Covid-19 pandemic at CLC Cerme Gresik. This study uses quantitative research with a survey approach. The sampling technique used was purposive sampling with a total of 35 students pursuing package C. Data collection techniques using questionnaires were carried out online using